Tools for farmers to policy makers to mainstream biodiversity for food and nutrition in local food systems: examples from Brazil, Kenya, Sri Lanka and Turkey - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The Biodiversity for Food and Nutrition (BFN) project pioneered an innovative approach to prioritization, research and promotion of biodiversity for food security and nutrition. Part of the project’s legacy has been the development of free, online resources that help others interested in promoting local biodiversity for improved nutrition. In addition, ongoing collaboration continues with international agencies and country-level partners to incorporate tools in relevant sectoral programmes and strategies and carry forward the positive momentum.